2004
DOI: 10.1111/j.1475-4754.2004.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Time‐Series Determination of the Rate of Diffusion of Water in Pachuca Obsidian*

Abstract: s (1960) article introducing an exciting, potentially precise and inexpensive method of dating obsidian artefacts has thus far failed to reach its potential. Numerous efforts to refine, improve and even redevelop the method since that time have similarly failed to achieve the original promise. Only within the last eight years have significant improvements been made, due to both improved analytical techniques and a better understanding of the hydration process. However, most of our mechanistic understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 127 publications
6
57
1
1
Order By: Relevance
“…1) with volume element equal to original volume minus new volume, etc., b) convert volume element to mass by way of density, c) assuming total water is evenly distributed calculate weight water (convert to moles) for each "layer" from known total water %, d) compute number of sites in each water "layer" necessary to come to equilibrium with labeled water (by moles), and e) sum deuterium values for layer by added layer. These incrementally calculated δ 2 H can be compared to times for experimental values of δ 2 H. By way of comparison of diffusion coefficients a value of around 8 x 10 -8 at 75°C is reported for obsidian (Anovitz et al, 2004 in figure 5) …”
Section: Recommended Ash Preparation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…1) with volume element equal to original volume minus new volume, etc., b) convert volume element to mass by way of density, c) assuming total water is evenly distributed calculate weight water (convert to moles) for each "layer" from known total water %, d) compute number of sites in each water "layer" necessary to come to equilibrium with labeled water (by moles), and e) sum deuterium values for layer by added layer. These incrementally calculated δ 2 H can be compared to times for experimental values of δ 2 H. By way of comparison of diffusion coefficients a value of around 8 x 10 -8 at 75°C is reported for obsidian (Anovitz et al, 2004 in figure 5) …”
Section: Recommended Ash Preparation Proceduresmentioning
confidence: 99%
“…Concluding that overprinting occurs with the new solvent front, they also note the apparent alteration of "intrinsic" water in the obsidian. This work is in addition to several low temperature diffusion studies employing SIMS (Anovitz et al, 2004;Anovitz et al, 2008;Riciputi 2002) providing useful perspectives on environmental fates of glasses as well as diffusion data.…”
mentioning
confidence: 99%
“…Direct measurement of EHT is the method to measure the soil temperatures from study sites and regions. It includes methods that bury artifact-embedded cells into study site (Ambrose, 1976;Anovitz et al, 2004;Ridings, 1991Ridings, , 1996Stevenson et al, 1998), and thermal cells that periodically record subsurface temperatures (Fredrickson et al, 2006;Jones et al, 1997). Indirect measurements of EHT, on the other hand, use temperatures recorded in surrogate station that is expected to have proximate climatic regime to study site (e.g., Friedman and Long, 1976;Lee, 1969;Rogers, 2007).…”
Section: Determination Of Effective Hydration Temperature (Eht) Is Crmentioning
confidence: 99%
“…The default model of time calculation using temperature and measured rim thickness is the Arrhenius equation (e.g., Long, 1976, 1978;Rogers, 2007). Through induced hydration experiments (e.g., Michels 1986;Michels et al 1983;Rogers and 4 Duke, 2011;Stevenson et al 1998) and application of new measurements of hydration rims, notably SIMS, the secondary ion mass spectrometry (e.g., Anovitz et al 1999Anovitz et al , 2004Liritzis, 2006;Stevenson et al, 2001), precise measurements of hydration rims quantified by the amount of hydration ions are provided. Thorough examinations of diffusion profiles have suggested that the diffusion of water molecules to create hydration rims is accurately described by the Fick"s law (e.g., Anovitz et al, 1999Anovitz et al, , 2004Liritzis, 2006).…”
mentioning
confidence: 99%
“…Liritzis and Laskaris 2011). However, other experiments challenge the square root of time dependence (Anovitz et al 1999(Anovitz et al , 2004Riciputi et al 2002), and some indicate that t 0.6 and t 0.7 are better statistical fits for experimental samples with varying proportions of intrinsic water (Stevenson et al 2013). "The diffusion of water is a complex and dynamic process" and the standard, constant model of diffusion (t 0.5 ) "may not be the best descriptor of the hydration process" (Stevenson et al 2013:3021).…”
Section: Introductionmentioning
confidence: 99%